Incidental Finding of Testicular Seminoma by 18F-Choline PET/CT in a Prostate Cancer Patient. (12th March 2022) - Calabrò, Anna; Bosio, Giovanni; Drera, Emma; Giubbini, Raffaele; Bertagna, Francesco
Abstract: An 80-year-old man with a history of prostate cancer, treated with radical prostatectomy and bilateral obturator nodal dissection, underwent an 18 F-choline PET/CT because of biochemical recurrence. The scan revealed an intense focal uptake in the right testicle. A subsequent orchifunicumlectomy demonstrated the presence of a classic seminoma. At present, 18 F-FDG PET/CT is useful for initial staging of testicular cancer and determining the viability of residual masses >3 cm after completion of treatment, especially in patients with seminoma.